2017
DOI: 10.3389/fneur.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Sleep Disorders in Parkinson’s Disease: From Research to Clinical Practice

Abstract: Sleep disorders (SDs) are one of the most frequent non-motor symptoms of Parkinson’s disease (PD), usually increasing in frequency over the course of the disease and disability progression. SDs include nocturnal and diurnal manifestations such as insomnia, REM sleep behavior disorder, and excessive daytime sleepiness. The causes of SDs in PD are numerous, including the neurodegeneration process itself, which can disrupt the networks regulating the sleep–wake cycle and deplete a large number of cerebral amines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 179 publications
(191 reference statements)
2
132
0
2
Order By: Relevance
“…Insomnia is thought to be the most common sleep disorder in PD and its prevalence ranges from 27% to 80%, part of the variability being due to differences in diagnostic criteria (5, 6). Sleep maintenance insomnia, including frequent awakenings/sleep fragmentation, is the most prevalent sleep disturbance in PD patients (81%) (5, 7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insomnia is thought to be the most common sleep disorder in PD and its prevalence ranges from 27% to 80%, part of the variability being due to differences in diagnostic criteria (5, 6). Sleep maintenance insomnia, including frequent awakenings/sleep fragmentation, is the most prevalent sleep disturbance in PD patients (81%) (5, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep maintenance insomnia, including frequent awakenings/sleep fragmentation, is the most prevalent sleep disturbance in PD patients (81%) (5, 7). Difficulty falling asleep (18%) and early awakenings (40%) are also encountered (5, 6). …”
Section: Introductionmentioning
confidence: 99%
“…The application of melatonin agonists (e.g., Ramelteon) might be a promising approach. More recent studies have revealed that rivastigmine might be another suitable pharmaceutical option for refractory RBD, as observed in small RCTs …”
Section: Established Therapiesmentioning
confidence: 87%
“…More recent studies have revealed that rivastigmine might be another suitable pharmaceutical option for refractory RBD, as observed in small RCTs. 37 CURRENT DEVELOPMENTS: DISEASE-MODIFYING APPROACHES General approaches…”
Section: Nonmotor Symptomsmentioning
confidence: 99%
“…В случаях ночной гипокинезии (пробуждения на фоне затруднений при поворотах в постели, ощущения «скованности») целесообразно повысить вечернюю дозу стандартного препарата, содержащего леводопу, либо назначить препараты, усиливающие ее дофаминергический эффект (энтакапон, ингибитор моноаминоксидазы В) [47][48][49][50]. Коррекции ночных симптомов БП и улучшению сна способствуют АДР прамипексол, ропинирол [51][52][53]. Однако на фоне приема АДР дневная сонливость может усиливаться, в связи с чем препараты этой группы рекомендуются преимущественно для вечернего приема в виде непролонгированной лекарственной формы.…”
Section: таблица 3 с р а в н е н и е п а ц и е н т о в с с н п -с б unclassified